ANALISIS USAHATANI NENAS DI DESA KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR - Muhammad Reza Nurhedianto; Shorea Khaswarina; Evy Maharani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
the purpose of this study: 1) find out the pineapple cultivation techniques in Kualu Nenas Village, 2) analyze the income of farmers in Kualu Nenas Village. Research in Kualu Nenas Village, Tambang District, Kampar Regency. Analysis of the data used is income analysis. The results showed that the production costs of pineapple farming in Kualu Nenas Village consisted of fixed costs and variable costs. The fixed cost of pineapple farming is Rp. 14,203,550.53 / year and variable costs are Rp. 21,316,493.33 / year. The total cost of producing pineapple farming is Rp. 14,203,550.53 / year with pineapple production of 41,356 and pineapple prices of Rp. 2,199 / piece. The average receipt of pineapple business in Kulau Nenas Village is Rp. 91,705,795.20 / year with a net income of Rp. 56,185,751.33 / yearKeywords: Pineapple Farmers, Revenue, Farm Efficiency